The Impact of ICT on Retrieval of Information Materials at Mbarara University of Science and Technology (MUST) Library- Mbarara District. - Atwongyere, Pamellah (Kabale University, 2023)
The purpose of the study was to assess the impact of ICT on the retrieval of information materials at Mbarara University of Science and Technology (MUST), Mbarara district. The study was guided by the specific objectives, which include finding out the role of ICT on retrieval of information materials, identifying the challenges facing the application of ICT on retrieval of information materials, and suggesting possible solutions to the challenges facing the application of 1CT on retrieval of information materials at the Mbarara University of Science and Technology library in Mbarara district. A study population of 300 people was used in this study. Using simple random and purposive sampling techniques, a total of 170 respondents were selected to participate in the study. The study used a mixed research design. In this study, data was collected using questionnaires and key informant interviews. A majority of 29% of participants in a study on the role of ICT in information retrieval in university libraries, specifically at Mbarara University, agreed that ICT brings innovation to information retrieval. The majority of participants (31%), it was discovered, were aware of the challenges associated with the use of ICT for retrieval of information materials in university libraries. The study findings also revealed that the majority (27% of the respondents) mentioned that training sessions should be provided to solve the challenges facing the application of ICT to the retrieval of information material in university libraries. It was recommended that academic libraries offer the tools needed for users to familiarize themselves with Information Communication and Technology to ease the retrieval of information materials. The novelty of this study was to document the impact of ICT on the retrieval of information materials. The study recommends that the government of Uganda should design strategies to train students and other library workers on retrieval of information materials.